Factors affecting the adaptation of cashless payment methods of small and medium enterprises in Tacloban City - Ayuste, Mackenzie Louisse D.; Macalalad, Kit Aubrey P. (2022)
This study focused on the factors affecting the adaptation of cashless payment methods of small and medium enterprises (SMEs) in Tacloban City. It also determined the various types of cashless payments, devices used to operate the cashless payments and preferences on cashless transactions of the SMEs. The researchers of this study used the combination of qualitative and quantitative approach in the process. The respondents were the SMEs in Tacloban City that are registered in the Department of Trade and Industry (DTI-R8). The study used the Slovin's formula to generate a sample size of 92, with a ninety percent (90%) Confidence Level. However, the researchers reached a total of 110 respondents who voluntarily participated in the study. The data gathered were processed and analyzed by the statistical method with the help of SPSS software.